Aplikasi Konsentrasi ZPT GA3 yang Berbeda untuk Peningkatan Kuantitas dan Kualitas Buah Jambu Air Madu Deli Hijau (Syzygium aqueum) - Hariyanti, Puput; Furoidah, Nanik (Program Studi Agroteknologi, 2023)
This study aims to determine the best concentration of ZPT GA3 to increase the quantity and quality of green deli honey water guava fruit. This research was carried out in Pancakarya Village, Ajung District, Jember Regency which was carried out from December 2021 to February 2022, with an altitude of 50 m above sea level. This study used a non-factorial randomized block design (RAK), with 5 different spraying treatments, repeated 5 times, a total of 25 research objects. The treatment studied was the concentration of GA3 (P) namely: P0 = Control, P1 = Concentration of 5 ppm , P2 = Concentration of 10 ppm, P3 = Concentration of 15 ppm, P4 = Concentration of 20 ppm. The data collected was analyzed by variance (Anova), if it was significantly different, it was continued with the BNT test at the 5% level using SPSS 20 For Windows. In determining the fruit to be sprayed using a random system. The results showed that the concentration of ZPT GA3 in the P4 treatment (concentration 20 ppm) gave optimal results for the sugar content of the fruit. GA3 concentration treatment gave results that were not significantly different for the parameters of fruit length, fruit diameter, number of perdompol fruit, fruit perdompol weight and unit weight of fruit.